A Conversation about Leadership and Quality with James Reinertsen and G. Ross Baker (Law & Governance, 2006)
[This article was originally published in Longwoods Review, Volume 4, Number 2.] James Reinertsen, MD, has worked as a physician, CEO and consultant on leadership, quality improvement and patient safety with leading healthcare systems around the world. What follow are excerpts from a conversation held at a dinner for healthcare leaders during the 7th National Conference on Quality in Toronto this February (2006). Reinertsen is a former CEO of Health System Minnesota and CareGroup, an academic and community hospital system in Boston. He currently heads The Reinertsen Group and leads the Institute for Healthcare Improvement's leadership development sector. The questions are posed by G. Ross Baker, PhD, professor in the Department of Health Policy, Management and Evaluation at the University of Toronto.